Microfluidic-driven biofabrication and the engineering of cancer-like microenvironments - Guimarães, Carlos F. (2022)
Despite considerable advances in cancer research and oncological treatments, the burden of the disease is still extremely high. While past research has been cancer cell centered, it is now clear that to understand tumors, the models that serve as a framework for research and therapeutic testing need to improve and integrate cancer microenvironment characteristics such as mechanics, architecture, and cell heterogeneity. Microfluidics is a powerful tool for biofabrication of cancer-relevant architectures given its capacity to manipulate cells and materials at very small dimensions and integrate varied living tissue characteristics. This chapter outlines the current microfluidic toolbox for fabricating living constructs, starting by explaining the varied configurations of 3D soft constructs microfluidics enables when used to process hydrogels. Then, we analyze the possibilities to control material flows and create space varying characteristics such as gradients or advanced 3D micro-architectures. Envisioning the trend to approach the complexity of tumor microenvironments also at higher dimensions, we discuss microfluidic-enabled 3D bioprinting and recent advances in that arena. Finally, we summarize the future possibilities for microfluidic biofabrication to tackle important challenges in cancer 3D modelling, including tools for the fast quantification of biological events toward data-driven and precision medicine approaches.